The investigation of the Staphylococcal Cassette Chromosome elements and Ciprofloxacin resistance in community Methicillin-Resistant Staphylococcus aureus Strains isolated in Western Australia - Wilson, Lynne (Curtin University, 2012)
In Western Australia, community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) continues to be a public health concern. Antibiotic resistance places additional burdens on the community and health-care systems. Updates in MRSA typing and molecular characterisation techniques have benefits in furthering understanding of the evolution and emergence of MRSA and ultimately result in improvements in the control and prevention of its spread. Molecular studies not only give an understanding of how MRSA evolve but enable typing to be improved so that isolates can be better identified and improvements made to their control and prevention of spread.Forty-five prototypes of CA-MRSA lineages isolated in Western Australia (WA) between 2003 and 2006 were used in this study and were provided by the Australian Collaborating Centre for Enterococcus and Staphylococcus Species (ACCESS) Typing and Research Unit, situated at PathWest Laboratory Medicine, Royal Perth Hospital, Perth, WA, which is also associated with Curtin University, School of Biomedical Sciences, Molecular Genetics Research Unit in a joint collaboration.The polymorphic region of the staphylococcal protein A (spa) gene is considered a useful typing tool for differentiation of MRSA. A spa typing protocol was trialled in this study. To assess the method’s suitability for typing MRSA, all 45 isolates were tested to determine their spa type. Significant diversity was revealed with 28 different spa types identified. The spa type t002 was the most prevalent (7/45). Except for one isolate, which could not be typed, spa types correlated with the multi locus sequence typing (MLST) and clonal complex designations of the 45 CA-MRSA. A major outcome of this study has been the introduction of a standardised protocol for spa typing as a routine typing technique by the ACCESS Typing and Research Unit.Ciprofloxacin and other fluoroquinolones have restricted use in the community with their availability more accessible in hospitals and at the initiation of this study it was unusual to find ciprofloxacin resistance in CA-MRSA, however, eight of the prototype CA-MRSA possessed high-level ciprofloxacin resistance. This study therefore included an investigation of genetic mutations that result in resistance to ciprofloxacin in S. aureus. The subset of eight isolates were tested for mutations in the genes grlA, grlB, gyrA and gyrB. Sequence analysis revealed that all eight isolates contained point mutations resulting in amino acid changes at codon 80 in grlA and at codon 84 in gyrA. Additional mutations were seen in three of the eight isolates analysed. One isolate contained previously unreported mutations that may be associated with ciprofloxacin resistance. It was concluded that the CA-MRSA isolates could have developed resistance to ciprofloxacin when the patients may have received fluoroquinolones as a course of treatment for infection caused by other organisms such as Gram-negative bacteria.The staphylococcal cassette chromosome mec (SCCmec) is a genomic resistance island found in MRSA and a primary typing target for their classification. The SCCmecs of a subset of eight of the 45 prototype CA-MRSA isolates that had novel classifications were analysed as part of this study. The novel classifications for four of the eight were resolved into already classified SCCmec types, three of them had novel sub-types, two remained novel and the SCC region of one, WA MRSA-40 was completely sequenced. The J regions of the SCCmec elements were found to be structurally heterogeneous leading to the conclusion that they are “hot spots” for recombination, rearrangement and acquisition of genetic information that enables adaptation for survival of the host cell in changing environments.The SCC region of WA MRSA-40 was found to be a composite genomic island named SCCmecWA MRSA-40-CI (GenBank Accession No JQ746621). The 72,522 bp SCCmecWA MRSA-40-CI, was found to be comprised of three elements, ΨSCCpls, SCCsorbitol and SCCmecVT (5C2&5) integrated in tandem into the attB site of the conserved hypothetical protein gene orfX. Each element was delineated by direct and inverted repeats. ΨSCCpls is 11,736 bp and was homologous to the ΔJ1 region of SCCmec type I which encodes a pls gene. SCCsorbitol is 19,497 bp, and encodes a sorbitol operon, type 1 restriction modification genes, and a ccrA2B2 gene complex together with seven open reading frames. This is the first time that a sorbitol operon has been reported in a SCC element and only the second time that a sorbitol operon has been reported in a staphylococcus, with it previously being found in S. carnosus. Acquisition of a sorbitol operon has been linked to dietary sorbitol usage. The SCCmec of WA MRSA-40 is 41,289 bp and is highly homologous with the SCCmec VT of the Taiwan strain PM1; it carries a class C2 mec complex and two ccrC1 gene complexes with ccrC1, alleles 8 and 2. An insertion sequence ISSau4-like was found in the J2 region. Polymorphisms that generated premature stop codons that would prevent transposase activity and stabilise the mec complex were detected in the sequences of the transposases of IS431L and IS431R that flank the mec region.In conclusion this study has provided important and relevant information on the utilisation of spa typing for routine typing, the genetics and emergence of ciprofloxacin resistance in CA-MRSA and the analysis of the SCCmec region and SCC elements of CA-MRSA, particularly WA MRSA-40.